2010
DOI: 10.1177/1753425910372000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cytokine-producing and antitumor activities of natural killer cells and macrophages by engagement of Toll-like and NOD-like receptors

Abstract: Macrophages and natural killer (NK) cells are important antitumor effectors by virtue of their ability to produce cytokines, chemokines and interferons (IFNs) and to mediate tumor cytotoxicity. Little is known about the impact of Toll-like receptor (TLR) and nucleotide binding and oligomerization domain (NOD)-like receptor (NLR) pathways on NK cell functions, and the role of TLRs and NLRs in macrophage activation is incompletely understood. In this study, we examined the capacities of expressed TLRs and NLRs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 61 publications
2
12
0
1
Order By: Relevance
“…First, we tested the above TLR agonists in their ability to reactivate latent HIV-1 in three other models of latency. Second, we tested their ability to induce IL-8 production in the promonocytic cell line THP-1 [ 27 ]. As shown in Additional file 1 : Figure S1A, Flagellin was able to reactivate latent HIV-1 in the J-Lat clone 10.6 as previously described [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, we tested the above TLR agonists in their ability to reactivate latent HIV-1 in three other models of latency. Second, we tested their ability to induce IL-8 production in the promonocytic cell line THP-1 [ 27 ]. As shown in Additional file 1 : Figure S1A, Flagellin was able to reactivate latent HIV-1 in the J-Lat clone 10.6 as previously described [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NOD2-like receptors (NLRs) belong to evolution-conserved pattern recognition receptors (PRRs) family locating in cytoplasm, closely related to responses, innate immunity and adaptive immunity [ 1 ]. NLRs are expressed in various cell types, including macrophage, neutrophils, epithelial and endothelial cells, dendritic cells, as well as in malignant tumors [ 19 ]. Genetic variations in NOD1 and NOD2 are associated with increased susceptibility to Crohn's disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a different study found that engagement of TLR3 on human CD8+ T cells had no effect on their cytolytic activity [19]. Human peripheral blood NK cells reportedly express high levels of TLR3, TLR7, and TLR9 and stimulation with ligands led to an increase in IFN-γ production [22]. In a mouse model of COPD, NK cells from smoke-exposed mice produced more IFN-γ following stimulation with the ligands for TLR3, TLR7, and TLR9 than NK cells from mice exposed to filtered air [23].…”
Section: Introductionmentioning
confidence: 99%